Consuming Life in Post-Bubble Japan - Cwiertka, Katarzyna J.; Machotka, Ewa (Amsterdam University Press, 2018)
The bursting of the economic bubble in the 1990s shook the very foundation of the post-war economic 'miracle' and marked the beginning of a gradual shift in the environmental consciousness of the Japanese. Yet, it by no means removed consumption from the pivotal position it occupied within Japanese society. Consuming Life in Post-Bubble Japan argues that consumption in Japan today is no longer simply a component of everyday economic activities, but rather a reflection of a society guided by the 'logic of late capitalism'. The volume pins down the contradictory nature of the setting in which consuming occurs in Japan today: the veneration of material comfort and convenience on the one hand, and the new rhetoric of recycling and energy conservation on the other. Theoretical insights developed as part of an art-historical enquiry, such as notions of socially engaged art and its critique, offer a new paradigm for investigating this dilemma. By combining case studies analysing the production and consumption of contemporary art with ethnographic material related to ordinary commodities and shopping, this volume provides a novel, transdisciplinary approach to exploring how a 'society of consumers' operates in post-bubble Japan and how contemporary life is a 'consuming project'.